SOSAS RESEARCH IDENTIFIED THE FOLLOWING SIX ISSUE AREAS AS BEING THE MAJOR DETERMINENTS OF PUBLIC OPINION TOWARDS THE SOCIAL ACCEPTABILITY OF SMOKING (Tufts Archival Research Center, 2007)
Research summary identifying the following six issue areas as being major determinants of public opinion towards the social acceptability of smoking: passive smoking, annoyance/courtesy, social cost, government intrusion, industry credibility, and image of smoker. Cites courses of action for the tobacco industry to promote their product.